Double Integrated-Buck Boost Converter versus Double Integrated-Buck Topology for LED Lamps - Damodaran, Sruthi; Nambiar, Renjini E; Jose, Jeanmary (Asian Journal of Electrical Sciences, 2019)
In this paper a comparative study between two different approaches for LED driving based on the double integrated buck boost and a double integrated Buck converter. It presents a single-stage, single-switch, transformer less ac/dc converter suitable for Led lighting applications. High Brightness Light Emitting Diodes (HB LEDs) can be seriously considered for replacing conventional halogen, incandescent and fluorescent lamps in general illumination including streetlights due to the rapid development in LED technology in recent years. In many offline applications, maintaining a high-power factor and low harmonics are of primary importance. Single stage power factor pre-regulation technology is mainly preferred in cost sensitive applications where power factor regulation is necessary, as adding additional power factor correction controller will surely increase the cost. Here a high-power-factor, long life integrated converter able to supply LED lamps from ac mains is presented. This topology integrates a buck-boost type power-factor correction (PFC) cell with a buck–boost dc/dc converter there by providing the necessary high input power factor and low Total Harmonic Distortion (THD). An isolation transformer increases complexities in the implementation of feedback and control. The proposed topology is non-isolated and hence much simpler in implementation. The main advantage of this converter is that this circuit uses only one controllable switch. The converter is used to provide power factor correction in streetlight application. A Double integrated buck converter finds application in fields of solid-state lighting. Buck Converter is widely used for step down dc-dc conversion when there is no isolation requirement. The narrow duty cycle of the buck converter limits its application for high step-down applications. The double integrated buck converter overcomes its limitation. This converter also provides high power factor and output current regulation. A Double integrated buck converter uses for the offline power supply for LED lighting based on the integration of a buck power factor corrector (PFC) and the tapped buck dc/dc converter having high step-down capability and good output current regulation. Due to the high reliability, the simple structure, and the low component count, the proposed topology effectively results to be very suitable for medium power solid-state lighting applications. From Comparative analysis of two circuits integrated double buck boost converter is found to be more efficient with high power factor and low THD.